Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/bem.20520
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral change related to Wenchuan devastating earthquake in mice

Abstract: It has been suggested that some animals are much more capable of perceiving certain kinds of geophysical stimuli which may precede earthquakes than humans, but the anecdotal phenomena or stories about unusual animal behaviors prior to an earthquake should be interpreted with objective data. During the Wenchuan magnitude 8.0 earthquake that happened in Wenchuan county (31.0 degrees north latitude, 103.4 degrees east longitude) of Sichuan province, China, on May 12, 2008, eight mice were monitored for locomotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…We believe that a truly reliable system for predicting strong earthquakes may have developed over the period of several hundred million years in certain animals, which is supported by several recent scientific studies reporting abnormal behavior in mice, rats, and toads in the range from 1 to 6 days before strong earthquakes (Yokoi et al, 2003;Li et al, 2009;Grant and Halliday, 2010;Lu-Lu et al, 2010;Grant et al 2011). Kirshvink (2000) argues that the evolutionary mechanism of exaptation (the ability to adapt or link a genetic pattern that evolved for one function for another role) may have produced a seismic-response system through the process of random mutation and natural selection.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We believe that a truly reliable system for predicting strong earthquakes may have developed over the period of several hundred million years in certain animals, which is supported by several recent scientific studies reporting abnormal behavior in mice, rats, and toads in the range from 1 to 6 days before strong earthquakes (Yokoi et al, 2003;Li et al, 2009;Grant and Halliday, 2010;Lu-Lu et al, 2010;Grant et al 2011). Kirshvink (2000) argues that the evolutionary mechanism of exaptation (the ability to adapt or link a genetic pattern that evolved for one function for another role) may have produced a seismic-response system through the process of random mutation and natural selection.…”
Section: Discussionmentioning
confidence: 72%
“…It is generally believed that similar anomalous animal behavior may have different causes and cannot be reproduced using the standard "input-sensor-response" approach. This reasoning is based on the fact that many past studies relied on subjective behavioral observations, such as anomalous locomotive activities in the circadian rhythms of mice (Yokoi et al, 2003;Li et al, 2009) or the quiescence or lack of spawning in toads (Grant and Halliday, 2010). However, if we rely on more objective biomedical signals and study the responses to certain stimuli believed to be related to earthquake buildup, we can apply the standard input-sensor-response method and identify precursors by analyzing the signals rather than the general behavior of the animals under study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that monitoring the earth magnetic eld can be used as a potential precursor for prediction of ND; in particular, EQ. Li et al [3] monitored 8 mice before, during, and after the 2008 Wenchuan earthquake of magnitude 8.0 in the Wenchuan county of Sichuan province, China. They observed changes in the locomotive activities of the mice 3 days prior to EQ, returning to their normal activities 6 days after the EQ.…”
Section: Changes In Animal Behavior Prior To An Earthquakementioning
confidence: 99%
“…However, most reports on UAB are based on qualitative rather than quantitative observations. As an example of quantitative UAB, changes in the locomotive activities of mice before large earthquakes were reported by Yokoi et al [20] and Li et al [21]. Grant et al [22] recently revealed, by the use of motion-triggered cameras, that wild animal activity in various species declined prior to the Contamana earthquake, with a magnitude (M) of 7.0.…”
Section: Introductionmentioning
confidence: 96%